Incorporating the Other: a historical examination of the productive processes of the Selva Central’s Yánesha people - Avendaño, Alex (2019)
A common theme among research on Amazonian indigenous economies has been the change of its 'traditional' character by processes of market insertion. The case of the Yánesha people, that inhabits the Palcazu valley, has not been the exception. In this space, the development of commercial livestock production and the establishment of three large protected natural areas have been followed by projects around environmental sustainability in the last 30 years. The present essay intends to take a different route for the interpretation on the economic and social change of this town. Based on the review of three historical moments, and an exploratory field trip, this text deals with the changes in the productive processes, contemplating ways of relating to the otherness of the indigenous Amazonian populations, characterized by a disposition of 'openness to the other'. In this way, the need to question the notions of insertion into the market as a simple passive integration will be argued; and, also, to approach theoretically to the ways in which the members of the Yánesha populations incorporate the foreign elements to their social life through practice.